2004
DOI: 10.1213/01.ane.0000093229.17729.6c
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Prolongs Spinal Anesthesia in Newborns: A Prospective Dose-Ranging Study

Abstract: Spinal anesthesia is suitable but often too short for complete surgery in newborns. This controlled, randomized, prospective, dose-ranging study was conducted in 75 neonates to test the hypothesis that clonidine could significantly lengthen bupivacaine spinal block. Clonidine 1 micro g/kg, added to spinal isobaric bupivacaine, doubles the duration of the block without significant deleterious hemodynamic or respiratory side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 7 publications
4
75
0
4
Order By: Relevance
“…Similar findings are observed in our study. Mean sedation scores were higher in Group B than Group A [10,12,13,14] and significant statistically i.e.=<0.0000001…”
Section: Ofmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar findings are observed in our study. Mean sedation scores were higher in Group B than Group A [10,12,13,14] and significant statistically i.e.=<0.0000001…”
Section: Ofmentioning
confidence: 80%
“…Various studies have shown that 1mcg/kg clonidine provides a significant improvement in spinal anaesthesia quality, duration and reduces the need of post-operative analgesic requirement without a significant side effects [1,2,3,4,5,10,11] . There is adequate evidence that α-2 adrenergic agonist clonidine given intrathecally produces anti nociceptive effects without any neurotoxicity and useful in the treatment of somatic pain [1,2,3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments and later human studies using neuraxial administration of clonidine have shown significant analgesia. 12,13,14,15 Further studies are required to establish clonidine as a safe and effective premedicant in children.…”
Section: Discussionmentioning
confidence: 99%
“…It produces analgesia by depressing the release of C-fiber transmitters and by hyperpolarization of postsynaptic dorsal horn neurons. 20,21 This antinociceptive effect may explain the prolongation of the sensory block when added to spinal anesthetics. The prolongation of the motor block of spinal anesthetics may result from the binding of α2-adrenoceptor agonists to motor neurons in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%